Frustrated Lewis Pair Chemistry of Chiral (+)‐Camphor‐Based Aminoboranes. Issue 31 (20th June 2013) - Lindqvist, Markus; Axenov, Kirill; Nieger, Martin; Räisänen, Minna; Leskelä, Markku; Repo, Timo
Abstract Dimethylamino‐(+)‐camphorenamine reacted with an equimolar amount of Piers' borane, HB(C6F5)2, to give the corresponding iminium–hydroborate zwitterionic salt. Being in equilibrium with the parent enamine–HB(C6F5)2 N–B pair, this salt was able to split hydrogen heterolytically, hydrogenating the iminium group in the molecule. Detailed studies revealed that the hydrogen splitting in this reaction proceeded through an intermolecular pathway leading to a bornylamine–HB(C6F5)2 adduct. When the starting enamine is present in excess over HB(C6F5)2, the produced bornylamine–HB(C6F5)2 adduct breaks up, eliminating free bornylamine and forming the initial camphorenamine– HB(C6F5)2 pair. This results in hydrogenation of the camphorenamine framework in a catalytic fashion.